Observation of an Even-Odd Asymmetric Transport in High Landau Levels - 刘广同 朱玉莹 王钦 庞远 樊洁 景秀年 姬忠庆 杨昌黎 吕力 杜瑞瑞 L. N. Pfeiffer K. W. West (Chinese physics letters, 2017)
Magnetotransport experiments including tilt fields are performed on ultrahigh mobility L-shaped Hall-bar samples of GaAs/AlGaAs quantum wells. The low-temperature longitudinal resistivity （ρxx） data demonstrate that a striking even-odd asymmetric transport exists along the [110] direction at half filling in N ≥ 2 high Landau levels. Although the origin for the peculiar even-odd asymmetry remains unclear, we propose that the coupling strength between electrons within the same Landau level and between the neighboring two Landau levels should be considered in future studies. The tilt field data show that the in-plane field can suppress the formation of both bubble and stripe phases.